2010
DOI: 10.1111/j.1651-2227.2010.01928.x
|View full text |Cite
|
Sign up to set email alerts
|

Secular trends of sports participation, sedentary activity and physical self‐perceptions in Hong Kong adolescents, 1995–2000

Abstract: Sports participation decreased and sedentary activities increased during the 5-year period. Physical self-perceptions did not change significantly, except an increase in being physically unfit was observed in girls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
3

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 30 publications
0
29
0
3
Order By: Relevance
“…Overall, however, we do not observe a consistent pattern of trends in TV viewing. A few studies have shown an increase in TV viewing or overall screen time [19,44,45] whereas other studies have found more stable or decreasing prevalence in TV viewing over time [21,38,46]. Two of the studies with increasing prevalence came from Chinese samples and might be not directly comparable to our cultural and secular context in terms of using screen-based media.…”
Section: Discussionmentioning
confidence: 96%
“…Overall, however, we do not observe a consistent pattern of trends in TV viewing. A few studies have shown an increase in TV viewing or overall screen time [19,44,45] whereas other studies have found more stable or decreasing prevalence in TV viewing over time [21,38,46]. Two of the studies with increasing prevalence came from Chinese samples and might be not directly comparable to our cultural and secular context in terms of using screen-based media.…”
Section: Discussionmentioning
confidence: 96%
“…The hot and humid weather in summer months may also discourage strenuous sports or exercise [28]. In addition, Hong Kong adolescents spend a great deal of time studying [29] and their recreational preferences are mostly sedentary digital entertainment such as computer use and digital games [4]. Therefore, it is of little surprise that some adolescents in Hong Kong fail to meet the current recommendation of 60 minutes of moderate-to-vigorous exercise daily, which may be an unrealistic goal for these youngsters.…”
Section: Discussionmentioning
confidence: 99%
“…However, most studies reported an increase in participation or no change, with a decline in participation evident in only one study of Hong Kong children. 25 …”
Section: Organised Sportmentioning
confidence: 97%
“…25 No whole sample percentages were provided, therefore the rate of change was −18 percentage points per decade for males and −6 percentage points per decade for females. The questionnaire was restricted to participation in 10 specified sports, which is a limitation as the popularity of these sports may have altered over the study period.…”
Section: Organised Sportmentioning
confidence: 99%